2008
DOI: 10.1007/s10393-008-0170-4
|View full text |Cite
|
Sign up to set email alerts
|

From “Us vs. Them” to “Shared Risk”: Can Animals Help Link Environmental Factors to Human Health?

Abstract: Linking human health risk to environmental factors can be a challenge for clinicians, public health departments, and environmental health researchers. While it is possible that nonhuman animal species could help identify and mitigate such linkages, the fields of animal and human health remain far apart, and the prevailing human health attitude toward disease events in animals is an "us vs. them" paradigm that considers the degree of threat that animals themselves pose to humans. An alternative would be the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…The One Health (OH) approach is based on the notion that human, animal, and environmental health are intimately connected and mutually dependent (Rabinowitz et al 2008; Dixon et al 2014). Consequently, advocates of this movement describe the need for a holistic and transdisciplinary approach when tackling complex global health issues with high societal values (American Veterinary Medical Association 2008; Greter et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The One Health (OH) approach is based on the notion that human, animal, and environmental health are intimately connected and mutually dependent (Rabinowitz et al 2008; Dixon et al 2014). Consequently, advocates of this movement describe the need for a holistic and transdisciplinary approach when tackling complex global health issues with high societal values (American Veterinary Medical Association 2008; Greter et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…So, there are numerous authors that have explored the potential of dogs and cats in this sense (Andrade et al, 2010;Baker et al, 2005;Calderón-Garciduenas et al, 2001;Heyder and Takenaka, 1996;Rabinowitz et al, 2008;Reif, 2011). However, in the case of exposure to POPs the results have been variable, because although some authors have suggested that cats seem to be adequate sentinels of human exposure to these contaminants (Ali et al, 2013;Dirtu et al, 2013;Guo et al, 2012), the role of dogs as such does not seem so clear Sévère et al, 2015).…”
Section: Introductionmentioning
confidence: 93%
“…The third major barrier to use of a "One Health" approach is the persistence of important gaps in scientifi c information and understanding about linkages between human and animal disease outcomes in response to environmental health threats (Rabinowitz et al 2008). As a result, when an outbreak of disease occurs in an animal population, there may be a delay in recognizing the human health relevance.…”
Section: Evidence Gapsmentioning
confidence: 99%